A Case Report on Hereditary Spherocytosis in a 22-Year-Old Female - A Pathan, Umme Habeeba (Journal of Pharmacy Practice and Community Medicine)
Hereditary spherocytosis is a rare genetically transmitted spherical shaped red blood cell disorder which leads to hemolytic anemia. The symptoms vary from asymptomatic to severe life-threatening anemia. The management includes splenectomy, blood transfusion and vitamin supplements. A 22-year-old female comes to tertiary care hospital with the complaints of fever, yellowish discoloration of eyes and urine. She was diagnosed with hereditary spherocytosis 10 years back and was continuously on blood transfusion. On day 1, her hemoglobin was 6.3 g/dL which falls under life-threatening anemia, total bilirubin was 7.9 g/dL, and direct bilirubin was 0.9 g/dL. She was given with blood transfusion for two days and hemoglobin level raised to 10 g/dL. This case presents life-threatening anemia and icterus associated with severe hereditary spherocytosis. The treatment in hereditary spherocytosis is quite challenging often because of its obscurity.
Keywords: Hereditary spherocytosis; Life-threatening anemia; Icterus; Transfusion